(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The digital transformation of society in the country, having formed the necessary basis for ensuring technological sovereignty, requires the executive and legislative authorities to accelerate the comprehensive regulatory support of state policy in this area. The state policy of digital transformation of Uzbekistan and its regulatory support are focused on the best world practices, claim to be an integrated approach, but a number of problems still remain: insufficient consistency, high volatility of the legal sector, insufficient development of technical regulation, the presence of contradictions in legislation, standards and technical regulations. The regulatory and legal framework for the digital transformation of business models in the economy of the republic, despite the measures taken, has not yet been formed at a level sufficient to solve the tasks set, which retains a number of barriers to digital development.